USING GAMES, MUSIC AND STORYTELLING TO ENGAGE YOUNG LEARNERS - Kodiraliyev Otabek (PEDAGOGS, 2024)
Abstract: It is important to use interactive methods such as games, music and stories to engage young students in the educational process, increase their interest and make the learning process more effective. These methods not only engage students’ attention, but also develop their creativity, logical thinking, and social skills. Integrating these elements into the learning process helps students feel comfortable and interested in learning.